SKRINING ANEMIA SEBAGAI UPAYA PENINGKATAN KESEHATAN IBU HAMIL DI PRAKTIK MANDIRI BIDAN TANJUNG DELITUA - Agnes Purba; Sharfina Haslin (Jukeshum: Jurnal Pengabdian Masyarakat, 2022)
Iron deficiency is the most common cause of anemia in pregnancy. Complications that can occur from anemia in pregnant women are postpartum hemorrhage, low birth weight babies, premature birth and impaired fetal growth and development. Iron tablets are given once a day for 90 days during pregnancy. The survey at the Tanjung Clinic District Deli Tua that every pregnant woman is given antenatal care, education about the health condition of the mother and fetus and the administration of iron tablets, however monitoring of maternal health conditions through checking hemoglobin must still be carried out to ensure the effectiveness of iron tablets given to pregnant women. For this reason, PkM is carried out as a screening for anemia in pregnancy. This community service was carried out at PMB Tanjung Deli Tua in the form of physical examinations for pregnant women, checking hemoglobin levels with an easy touch device, giving iron tablets and providing education about the benefits and how to consume iron tablets correctly. The results obtained were that the majority of LiLA of pregnant women were 23.5 cm (95.4%) and the majority of pregnant women were secondary (52.2%). Then it was found out of 46 pregnant women who were examined 1 person (2%) had anemia. Through this PkM activity, it is necessary to collaborate with the nearest puskesmas to provide additional food for pregnant women who experience anemia and KEK.